TINJAUAN LITERATUR TENTANG E-MODUL BAHASA INGGRIS DIGITAL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA - Sari, Etika; Riswandi; Ari Nurewni; Rangga Firdaus (UNDIKMA, 2026)
The use of digital-based e-modules has become an important innovation in English language learning to effectively improve students' skills. This literature study examines various aspects of the development and application of multimodal and gamified e-modules that can improve reading and speaking skills. This research uses the semantic literature review method to analyze various literatures. Data collection is carried out through systematic searches in various academic databases, google scholar, sciencedirect, data analysis is carried out with a semantic analysis approach which includes theme identification, coding and categorization, literature synthesis, and interpretation of results. Research shows that interactive and engaging e-modules can facilitate independent and distance learning, and overcome the challenge of limited conventional learning resources. However, successful implementation requires training for teachers and provision of adequate technological infrastructure. In addition, innovative approaches such as multimodal and gamification are instrumental in increasing student engagement. Recommendations from this study emphasize the need for collaboration between the government, educational institutions and the community to optimize the use of digital technology in English language learning in order to improve the quality and effectiveness of the learning process in a sustainable manner